Consideration of the Role of Guanxi in the Ethical Judgments of Chinese Managers - Ho, Cynthia (Journal of business ethics, 2010)
The importance of personal connections and relationships, or guanxi when doing business with the Chinese is widely acknowledged amongst Western academics and business managers alike. However, aspects of guanxi-related behaviours in the workplace are often misunderstood by Westerners with some going so far as to equate guanxi with forms of corruption. This study extends earlier study of Tan and Snell: 2002, Journal of Business Ethics 41(December), 361–384) in its investigation of the underlying modes of moral reasoning in ethical decisions relating to aspects of guanxi, amongst Hong Kong managers. Managers’ ethical judgements and underlying moral reasoning relating to a series of guanxi-related behaviours were recorded. Content analysis yielded categories that correspond with categories of moral reasoning described in Kohlberg’s (1969, Handbook of Socialization Theory and Research, Rand McNally, Chicago, pp. 347–480) model. As hypothesised, it was found that harsher ethical evaluations of guanxi-related behaviours were positively correlated with the stage of moral reasoning. The most common types of reasoning were those corresponding to Kohlberg’s stages four and five which relate to moral reasoning based on law and order, and on reason rather than emotion. Stage 6, concerned with more universalistic approaches to moral reasoning, was utilised considerably less, consistent with popularly held beliefs of the relativistic nature of Chinese ethics.